2010
DOI: 10.1111/j.1469-8137.2009.03140.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of retrotransposons in synthetic allotetraploid tobacco

Abstract: Summary• Allopolyploidy is a major driving force in plant evolution and can induce rapid structural changes in the hybrid genome. As major components of plant genomes, transposable elements are involved in these changes. In a previous work, we observed turnover of retrotransposon insertions in natural allotretraploid tobacco (Nicotiana tabacum). Here, we studied the early stages of allopolyploid formation by monitoring changes at retrotransposon insertion sites in the Th37 synthetic tobacco.• We used sequence-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 65 publications
1
116
5
Order By: Relevance
“…Such a burst in transpositional activity has been proposed in allopolyploids, based on the fact that all genes are duplicated and the genome can therefore tolerate higher levels of TE activity [82]. An increase in the copy number of a Tnt1 retrotransposon was detected in allotetraploid tobacco [83], but no similar transposition burst was detected after genome doubling in the allopolyploid Spartina anglica [84]. In synthesized allohexaploid wheat (T. aestivum), both AFLP-based analysis and small RNA high-throughput sequencing data showed that the abundance of Veju long terminal repeats decreased in allopolyploid wheat and is associated with a decrease in CG methylation [85,86].…”
Section: (E) Transposons and Noveltymentioning
confidence: 97%
“…Such a burst in transpositional activity has been proposed in allopolyploids, based on the fact that all genes are duplicated and the genome can therefore tolerate higher levels of TE activity [82]. An increase in the copy number of a Tnt1 retrotransposon was detected in allotetraploid tobacco [83], but no similar transposition burst was detected after genome doubling in the allopolyploid Spartina anglica [84]. In synthesized allohexaploid wheat (T. aestivum), both AFLP-based analysis and small RNA high-throughput sequencing data showed that the abundance of Veju long terminal repeats decreased in allopolyploid wheat and is associated with a decrease in CG methylation [85,86].…”
Section: (E) Transposons and Noveltymentioning
confidence: 97%
“…DNA is integrating into the nuclear genome from a variety of sources, including (retro)transposable elements, viral DNA, plastid and mitochondrial sequences. Furthermore, stress and polyploidy activate retrotransposon transcription and integration (Grandbastien, 1998;Petit et al, 2010). The inevitable genome enlargement is counteracted by mechanisms which excise DNA (e.g.…”
Section: Chromosome Structure -Less Dynamic Genomes In Coniferalesmentioning
confidence: 99%
“…carrying chromosomal translocations, deletions and duplications; Lim et al, 2006;Gaeta et al, 2007). Even in synthetic polyploids, changing copy numbers of repeats can be observed (Petit et al, 2010;Renny-Byfield et al, 2011). From these variants, selection favours the most fertile individuals where chromosome pairing and segregation are regular.…”
Section: Genetic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the last polyploidy in the sorghum (Sorghum bicolor) lineage was about 70 million years ago (mya), many millions of years before the origin and broad diversification of the grass family (Paterson et al, 2004). Beyond doubling genome size, polyploidy has been observed to serve as a 'genomic shock' that activates TE amplification and resultant genome rearrangement, possibly through altering the balance in their epigenetic silencing (O'Neill et al, 1998;Ozkan et al, 2001;Madlung et al, 2005;Parisod et al, 2009;Petit et al, 2010). After polyploidy, an eventual diploidization process occurs that leads to exclusive disomic inheritance and the loss of a subset of the genes that were, for instance, doubled in nuclear copy number by a diploid to tetraploid polyploid event.…”
Section: Introductionmentioning
confidence: 99%